2023
DOI: 10.3390/plants12040974
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Soil Bacterial Communities under Canopies of Pinus tabulaeformis and Populus euramericana in a Reclaimed Waste Dump

Abstract: To compare the effects of different remediation tree species on soil bacterial communities and provide a theoretical basis for the selection of ecosystem function promotion strategies after vegetation restoration, the characteristic changes in soil bacterial communities after Pinus tabulaeformis and Populus euramericana reclamation were explored using high-throughput sequencing and molecular ecological network methods. The results showed that: (1) With the increase in reclamation years, the reclaimed soil prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Regarding various environmental conditions, soil is the most important factor in stimulating secondary metabolites, as it controls the movement and availability of water, air, and nutrients (Atyane et al, 2016 ; Yang et al, 2018 ; Xiao et al, 2022 ). Several studies have shown that soil type and cultivar influence the available nitrogen, phosphorus, potassium, and organic carbon content of rhizosphere soil, thereby affecting rhizosphere microbial communities, plant growth, and secondary metabolites (Sampaio et al, 2016 ; Ren et al, 2022 ; Hou et al, 2023 ). Organic matter (OM) can promote the formation of soil structure, improve the fertilizer holding capacity and buffer capacity of the soil, promote the growth and development of plants, and affect secondary metabolites (Witzgall et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding various environmental conditions, soil is the most important factor in stimulating secondary metabolites, as it controls the movement and availability of water, air, and nutrients (Atyane et al, 2016 ; Yang et al, 2018 ; Xiao et al, 2022 ). Several studies have shown that soil type and cultivar influence the available nitrogen, phosphorus, potassium, and organic carbon content of rhizosphere soil, thereby affecting rhizosphere microbial communities, plant growth, and secondary metabolites (Sampaio et al, 2016 ; Ren et al, 2022 ; Hou et al, 2023 ). Organic matter (OM) can promote the formation of soil structure, improve the fertilizer holding capacity and buffer capacity of the soil, promote the growth and development of plants, and affect secondary metabolites (Witzgall et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%